Studying topography effects in remotely sensed data on the accuracy of GPS reading - ذنون شهاب الحمامي, عاهـد (Al-Adab Journal, 2018)
Pine forest identification and discrimination for mapping purpose in the GPS device is one of the best tools recently used in determining the coordinates and elevation for any spot on the Earth's surface.The cheap cost and ease offered by the GPS devices made them widely used these days for the purposes of navigation , mobility , locating specific points and the preparation of maps .Data from a Coarse Acquisition Global Positing System (GPS) map-grade receiver were evaluated to assess the accuracy of field point.Many studies have focused on the accuracy of GPS units under ideal data collection conditions. Ideal field data conditions are often less than Ideal because of mountainous topography, heavy forest cover, or other obstructions which block satellite signals from the receiver.The terrains are of the fixed factors affecting the coordinate calculations , but we can still using time for enhancing coordinate registration.We examined GPS accuracy in a certain procedure to employ the use of the time factor for minimizing the impact of an error due to dilution of accuracy (DOP) as little as possible, taking in consideration the elevations of the surrounding terrains around the study point .This method reduces the error rate to a minimum on both horizontal and vertical distances by utilizing the appropriate time frame which may offers better geometrical alignment angles of the satellites with the GPS handheld device.